Modifications of Plasma Membrane Organization in Cancer Cells for Targeted Therapy - Anna Choromańska; Agnieszka Chwiłkowska; Julita Kulbacka; Dagmara Baczyńska; Nina Rembiałkowska; Anna Szewczyk; Olga Michel; Agnieszka Gajewska-Naryniecka; Dawid Przystupski; Jolanta Saczko (Molecules, 2021)
Modifications of the composition or organization of the cancer cell membrane seem to be a promising targeted therapy. This approach can significantly enhance drug uptake or intensify the response of cancer cells to chemotherapeutics. There are several methods enabling lipid bilayer modifications, e.g., pharmacological, physical, and mechanical. It is crucial to keep in mind the significance of drug resistance phenomenon, ion channel and specific receptor impact, and lipid bilayer organization in planning the cell membrane-targeted treatment. In this review, strategies based on cell membrane modulation or reorganization are presented as an alternative tool for future therapeutic protocols.